Study Of Prevalence Of Chondromalacia Patella In Long Route Bus Drivers. - Patil, Shreya; Jadhav, Aditi; Bamane, Disha (Journal of Neonatal Surgery, 2025)
Introduction:Chondromalacia patella is characterized by the softening or damage to the patellar under surface is a common condition associated with knee pain and dysfunction.Long route bus drivers ,who are required to sit with knee flexed for prolong time and frequently use their legs for operating the vehicle,including pressing the clutch and break pedals,which may contribute to mechanical stress on knee joint.Due to prolonged,repetitive nature of these action,so drivers are at increased risk for developing musculoskeletal disorder including Chondromalacia patella. Methodology: A observational study conducted with 97 participants aged between 25 to 45 Each participant had taken part in a single test of Clarke's sign, Kujala score questionnaire and NPRS Scale. For assessing knee functions Kujala score questionnaire was performed. All the outcome measures were assessed on same day for each participants by the same examiner. Result: The result of the study was generated using SPSS version 28 MS Excel 2016. This study shows that In NPRS, pain ratings are significantly higher during movements of activity (8.06) compared to at rest (3.52). By Kujala score questionnaire we got to know that 21% of patients experienced severe Anterior knee pain, 55% of patients (good + fair) experienced mild to moderate knee pain and 27% of patients experienced minimal or no pain. Conclusion: The results of this study provide valuable insights into the pain and experiences of patients with anterior knee pain. Notably, This finding highlights the impact of physical activity on exacerbating anterior knee pain, emphasizing the need for effective management strategies to mitigate this pain during daily activities.Furthermore, the Kujala score questionnaire revealed that findings underscore the heterogeneity of pain experiences among patients with anterior knee pain, emphasizing the importance of personalized treatment approaches that cater to the unique needs and pain profiles of individual patients. Overall, this study contributes to a deeper understanding of anterior knee pain and informs the development of effective management strategies to improve patient outcomes